Effects of Linguistic Distance on Cognitive Skills, Health, and Social Outcomes in Canadian Immigrants - Kuperman, Victor (Frontiers in Political Science, 2022)
Learning languages is more difficult if they are more distant (dissimilar) from the person's first language. For immigrants, a greater distance between their L1 and official languages of their host country impedes integration. Using microdata from the PIAAC survey in 2012, we quantified the cognitive, and socio-economic impact of linguistic distance on a sample of 2,018 immigrants to Canada representing 12 diverse languages. Speakers of languages more distant from English or French showed lower literacy scores, worse health and weaker community engagement, yet numeracy and income were unaffected. We discuss causes and implications of these findings for immigration experience.